Observation of the radiative decay D*+-> D+gamma - Bartelt, J; Csorna, SE; Jain, V; McLean, K; Marka, S; Godang, R; Kinoshita, K; Lai, I; Pomianowski, P; Schrenk, S; Bonvicini, G; Cinabro, D; et al. (1998)
We have observed a signal for the decay D*+ → D+ γ at a significance of 4 standard deviations. From the measured branching ratio B(D*+ → D+ γ)/B(D*+ → D+ π0) = 0.055 ± 0.014 ± 0.010 we find B(D*+ → D+ γ) = 0.017 ± 0.004 ± 0.003, where the first uncertainty is statistical and the second is systematic. We also report the highest precision determination of the remaining D*+ branching fractions.